Virtual health connect: A community-based immunisation scheduler and manager - Keng, Siang Ooi; Yu-N, Cheah (2013)
According to the World Health Organisation (WHO), there were 28,950 children in Malaysia who did not receive full immunisation,given by the Malaysian government for free, by the age of 7 in 2011 alone.Current manual or paper-based systems are no longer effective nor efficient in keeping track of the immunisation schedules, and in reminding parents regarding their children‘s immunisation schedules.Virtual Health Connect (VHC) is a community-based lightweight web-based solution that helps to manage children‘s immunisation schedules automatically and sends short message service (SMS) reminders to parents when their children‘s upcoming immunisation dates draw near.Healthcare personnel can also generate monthly reports on immunisation coverage and trace appointment defaulters easily, saving administrative time and effort.